(untitled) (Journal of Educational Sciences, 2024)
This article presents the key advantages and experiences of forming digital competence and utilizing new pedagogical approaches in the education and training of future biology teachers, along with the results of research. Currently, it is crucial for future biology teachers not only to absorb vast amounts of information but also to become qualified, high-quality professionals capable of applying their knowledge in real-life contexts and meeting the requirements set by educational institutions. Therefore, the theoretical justification of forming digital competence for future biology teachers in blended learning environments, as well as assessing its effectiveness through research based on the development of methodologies, underscores the significance of this article. The identification of an effective research method was conducted based on a literature review. To achieve this, articles by researchers from various countries, both near and far abroad, were selected through the University Library System. Additionally, students enrolled in the educational program 6B01505 - ‘Teacher Training in Biology’ were tasked with utilizing effective methods and new technologies aimed at fostering students’ knowledge, skills, and competencies in line with the content of the academic discipline ‘Teaching Methodology in Biology’. Successful outcomes were achieved. Comprehensive considerations were given to providing students with suitable educational platforms for learning teaching methods. “The practical significance of the research lies in the development of a digital educational environment using MOODLE, based on the subject of ‘Teaching Methodology in Biology.’ This involved preparing presentations and video recordings of lectures that define the content of the topic. Additionally, the article comprehensively presents the advantages of services and the effectiveness of utilizing educational platforms.” Keywords:blended learning, digital competence, digital education, digital transformation, educational environment, interactive technologies.